Pelvic Congestion Syndrome: Systematic Review of Treatment Success - Brown, Candace L.; Rizer, Magda; Alexander, Ryan; Sharpe, Emerson E., III; Rochon, Paul J. (Seminars in Interventional Radiology, 2018)
Pelvic venous insufficiency is now a well-characterized etiology of pelvic congestion syndrome (PCS). The prevalence of CPP is 15% in females aged 18 to 50 years in the United States and up to 43.4% worldwide. In addition to individual physical, emotional, and quality-of-life implications of CPP, there are profound healthcare and socioeconomic expenses with estimated annual direct and indirect costs in the United States in excess of 39 billion dollars. PCS consists of clinical symptoms with concomitant anatomic and physiologic abnormalities originating in venous insufficiency. The etiology of PCS is diverse involving both mechanical and hormonal factors contributing to venous dilatation (>5 mm) and insufficiency. Factors affecting the diagnosis of PCS include variance of causes and clinical presentations of pelvic pain and relatively low sensitivity of noninvasive diagnostic imaging and laparoscopy to identify insufficiency compared with catheter venogram. A systematic review of the literature evaluating patient outcomes following percutaneous treatment of PCS is presented.
Keywords: interventional radiology; pelvic congestion syndrome; pelvic pain; venous reflux; embolization